Satellite cells in human skeletal muscle plasticity - Snijders, Tim; Nederveen, Joshua P.; McKay, Bryon R.; Joanisse, Sophie; Verdijk, Lex B.; van Loon, Luc J. C.; Parise, Gianni (Frontiers in Physiology, 2015)
Skeletal muscle satellite cells are considered to play a crucial role in muscle fiber maintenance, repair and remodelling. Our knowledge of the role of satellite cells in muscle fiber adaptation has traditionally relied on in vitro cell and in vivo animal models. Over the past decade, a genuine effort has been made to translate these results to humans under physiological conditions. Findings from in vivo human studies suggest that satellite cells play a key role in skeletal muscle fiber repair/remodelling in response to exercise. Mounting evidence indicates that aging has a profound impact on the regulation of satellite cells in human skeletal muscle. Yet, the precise role of satellite cells in the development of muscle fiber atrophy with age remains unresolved. This review seeks to integrate recent results from in vivo human studies on satellite cell function in muscle fiber repair/remodelling in the wider context of satellite cell biology whose literature is largely based on animal and cell models.